PENERAPAN MODEL KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR DAN KEAKTIFAN SISWA PADA ELEMEN GAMBAR TEKNIK KELAS X DPIB DI SMK N 2 BINJAI - Syahputri, Tria Eka Syahputri; Kemala Jeumpa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the improvement of student learning outcomes in the engineering drawing element of class X DPIB SMK Negeri 2 Binjai This research aims to improve learning outcomes and student activity through the application of a Group Investigation (GI) type cooperative learning model in the subject of the Fundamentals of the Engineering Drawing Element Expertise Program class X DPIB at SMK Negeri 2 Binjai Academic Year 2025/2026. This research is a Class Action Research (PTK) which is carried out in two cycles, where each cycle consists of planning, implementation, observation, and reflection stages. The subjects of the study were 34 students of class X DPIB-1. The data collection technique is carried out through learning outcome tests to measure the cognitive realm and observation sheets to assess student activity during the learning process. The data of this research was obtained from the tests carried out were test validity tests, test difficulty index, question differentiation and test reliability. . The tool used in collecting data in this study is a learning test, which can be seen from the learning activity of students in the first cycle of meeting 1 which has an average score of 71.03 while in the second cycle of the meeting there is a significant increase, namely obtained with an average score of 82.72, it can be seen that the increase occurred between cycle I and cycle II. The results of this study show that there is a significant increase in learning outcomes from cycle I to cycle II. In the first cycle, the average score of students was 56.91. while in cycle II, the average score of students increased to 88.02. So it can be seen that the increase that occurred between cycle I and cycle II was 28.11%. This proves that the Group Investigation-type cooperative learning model can increase learning outcomes and activeness in engineering drawing elements.